Distinguishing Target From Distractor in Stroop, Picture–Word, and Word–Word Interference Tasks - Schmalz, Xenia; Treccani, Barbara; Mulatti, Claudio (Frontiers in Psychology, 2015)
Lexical selection – both during reading aloud and speech production – involves selecting an intended word, while ignoring irrelevant lexical activation. This process has been studied by the use of interference tasks. Examples are the Stroop task, where participants ignore the written color word and name the color of the ink, picture-word interference tasks, where participants name a picture while ignoring a super-imposed written word, or word-word interference (WWI) tasks, where two words are presented and the participants need to respond to only one, based on an pre-determined visual feature (e.g., color, position). Here, we focus on the WWI task: it is theoretically impossible for existing models to explain how the cognitive system can respond to one stimulus and block the other, when they are presented by the same modality (i.e., they are both words). We describe a solution that can explain performance on the WWI task: drawing on the literature on visual attention, we propose that the system creates an object file for each perceived object, which is continuously updated with increasingly complete information about the stimulus, such as the task-relevant visual feature. Such a model can account for performance on all three tasks.